Activating variants in PDGFRB result in a spectrum of disorders responsive to imatinib monotherapy. Issue 7 (5th June 2020) - Wenger, Tara L.; Bly, Randall A.; Wu, Natalie; Albert, Catherine M.; Park, Julie; Shieh, Joseph; Chenbhanich, Jirat; Heike, Carrie L.; Adam, Margaret P.; Chang, Irene; Sun, Angela; Miller, Danny E.; et al.
Abstract: More than 50 individuals with activating variants in the receptor tyrosine kinase PDGFRB have been reported, separated based on clinical features into solitary myofibromas, infantile myofibromatosis, Penttinen syndrome with premature aging and osteopenia, Kosaki overgrowth syndrome, and fusiform aneurysms. Despite their descriptions as distinct clinical entities, review of previous reports demonstrates substantial phenotypic overlap. We present a case series of 12 patients with activating variants in PDGFRB and review of the literature. We describe five patients with PDGFRB activating variants whose clinical features overlap multiple diagnostic entities. Seven additional patients from a large family had variable expressivity and late‐onset disease, including adult onset features and two individuals with sudden death. Three patients were treated with imatinib and had robust and rapid response, including the first two reported infants with multicentric myofibromas treated with imatinib monotherapy and one with a recurrent p.Val665Ala (Penttinen) variant. Along with previously reported individuals, our cohort suggests infants and young children had few abnormal features, while older individuals had multiple additional features, several of which appeared to worsen with advancing age. Our analysis supports a diagnostic entity of a spectrum disorders due to activating variants in PDGFRB . Differences in reported phenotypes can be dramatic and correlate with advancing age, genotype, and to mosaicism in some individuals.